2013
DOI: 10.1097/aog.0000000000000020
|View full text |Cite
|
Sign up to set email alerts
|

Cesarean Delivery and Cerebral Palsy

Abstract: A review of the literature does not support the use of elective or emergency cesarean delivery to prevent cerebral palsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 27 publications
1
26
1
2
Order By: Relevance
“…However, in CP infants born almost matured at near term such in the present subjects, adverse conditions involving acute utero-placental under-perfusion including placental abruption and uterine rupture, and required acute delivery due to NRFS were more associated with CP rather than chronically progressive adverse condition such as fetal growth restriction and hypertensive disorder. Previous meta-analysis demonstrated that newborns delivered by emergency Cesarean section at term were more likely to have CP (1.6; 95%CI 1.05–2.44) [ 15 ]. It is considered that this result showed risk factors for CP in association with emergency Cesarean section, with the likely confounding that acute or chronic fetal compromise would often precipitate this intervention [ 15 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in CP infants born almost matured at near term such in the present subjects, adverse conditions involving acute utero-placental under-perfusion including placental abruption and uterine rupture, and required acute delivery due to NRFS were more associated with CP rather than chronically progressive adverse condition such as fetal growth restriction and hypertensive disorder. Previous meta-analysis demonstrated that newborns delivered by emergency Cesarean section at term were more likely to have CP (1.6; 95%CI 1.05–2.44) [ 15 ]. It is considered that this result showed risk factors for CP in association with emergency Cesarean section, with the likely confounding that acute or chronic fetal compromise would often precipitate this intervention [ 15 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous meta-analysis demonstrated that newborns delivered by emergency Cesarean section at term were more likely to have CP (1.6; 95%CI 1.05–2.44) [ 15 ]. It is considered that this result showed risk factors for CP in association with emergency Cesarean section, with the likely confounding that acute or chronic fetal compromise would often precipitate this intervention [ 15 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La capacité d'une ré gression de Poisson de reconnaître les nombres individuels de cas de PC et de naissances vivantes permet de constater qu'avec une puissance adé quate, les donné es rapporté es par Racinet et al montrent une diminution significative modé ré e de la pré valence de PC avec le taux de cé sariennes dans les dé partements concerné s. Cette analyse ré trospective est seulement gé né ratrice d'hypothè se à confirmer ou infirmer avec une é tude suffisamment puissante sur des donné es individuelles (qui comprennent de pré fé rence celles pour des facteurs de confusion importants). À cet é gard, Racinet et al ont comparé leurs ré sultats avec ceux d'une mé ta-analyse de 13 é tudes observationnelles [6]. Il s'agit né anmoins d'une mé ta-analyse sur des estimations univarié es (nombres absolus de cas de PC et de té moins sans PC né s avec ou sans cé sarienne).…”
Section: Racinet Et Al Ont Analysé Sept Ansunclassified
“…Хотя тер-мин «ДЦП» и не отражает сущности имеющихся при этом заболевании нарушений, его широко используют в мировой литературе, и другого понятия, всесторонне характеризующего данные патологические состояния, до настоящего времени не предложено. Согласно результатам популяционно-эпидемиологических исследований, частота ДЦП составляет 1,9-2,7 случаев на 1000 детей [3,16,31], однако существуют единичные публикации и о более высокой распространенности заболевания -до 10 на 1000 новорожденных [27].…”
unclassified